The Mystery of Handprints: Assesment and Correlation of Dermatoglyphics with Early Childhood Caries A Case-Control Study - Navit, Saumya (J Clin Diagn Res, 2015)
BACKGROUND: It has been acknowledged that genetics play a significant role in determination of dermatoglyphic patterns. Since caries is a multifactorial disease with the influence of genetic pattern, this study was undertaken to assess dermatoglyphic patterns and correlate them with early childhood caries. AIM: The aim of the study was to determine the association and correlation of dermatoglyphic patterns with early childhood caries. MATERIALS AND METHODS: The study sample consisted of 100 children aged between 3 and 6 years, divided into two groups of 50 children each. The deft score was evaluated to select the experimental group and control group. Finger and palm prints were recorded using the ink method described by Cummins and Midlo. The handprints obtained were checked for their clarity with a magnifying glass (×2) and coded. The presence of core and the triradii of the dermatoglyphic pattern were checked thoroughly to include the handprint in the study. A total of 1000 digital prints and 200 palmar prints were obtained. RESULTS: The presence of whorls in the index finger of the right hand predicts significantly lower risk of caries in children (male and female; combined). Presence of whorls in the ring finger of the right hand predicts significantly lower risk of caries in female children. Statistically no correlation between atd angle and early childhood caries was obtained from the present data. CONCLUSION: The results obtained from the present study creates a notion on the validity of the results of the previous studies and point them to be chance findings. Due to increasing acceptability of dermatoglyphics as a diagnostic tool for congenital diseases, further large scale extensive research should be undertaken to evaluate the role of the same in children with Early Childhood Caries (ECC).